2020
DOI: 10.1002/cssc.202002009
|View full text |Cite
|
Sign up to set email alerts
|

Can CO2 and Steam React in the Absence of Electrolysis at High Temperatures?

Abstract: The fundamental question of whether CO2 can react with steam at high temperatures in the absence of electrolysis or high pressures is answered. These two gases are commonly co‐present as industrial wastes. Herein, a simple experiment by flowing CO2 and steam through a CaCl2 matrix at 500–1000 °C and atmospheric pressure was designed. Comprehensive characterizations and density functional theory calculations were conducted. Meanwhile, this study aims to recover HCl from CaCl2 via a low‐emission oxy‐pyrohydrolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Zhou et al investigated the HCl generation rate from CaCl 2 by flowing steam on the CaCl 2 surface with and without CO 2 . 16 The release extent of the HCl under the interaction of CO 2 and steam was significantly facilitated by up to four times the value obtained without CO 2 . Kondo et al studied the recovery of chlorine gas from CaCl 2 by blowing oxygen into molten CaCl 2 at temperatures above 950 °C.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…Zhou et al investigated the HCl generation rate from CaCl 2 by flowing steam on the CaCl 2 surface with and without CO 2 . 16 The release extent of the HCl under the interaction of CO 2 and steam was significantly facilitated by up to four times the value obtained without CO 2 . Kondo et al studied the recovery of chlorine gas from CaCl 2 by blowing oxygen into molten CaCl 2 at temperatures above 950 °C.…”
Section: Introductionmentioning
confidence: 88%
“…Zhou et al calculated the surface energy of four index surfaces and concluded that the (110) surface is the most stable CaCl 2 surface. 16…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations